The pioneer factor PBX1 is a novel driver of metastatic progression in ERα-positive breast cancer. - Magnani,L; Patten,DK; Nguyen,VTM; Hong,SP; Steel,JH; Patel,N; Lombardo,Y; Faronato,M; Gomes,AR; Woodley,L; Page,K; Guttery,D; et al. (Oncotarget, 2015)
Over 30% of ERα breast cancer patients develop relapses and progress to metastatic disease despite treatment with endocrine therapies. The pioneer factor PBX1 translates epigenetic cues and mediates estrogen induced ERα binding. Here we demonstrate that PBX1 plays a central role in regulating the ERα transcriptional response to epidermal growth factor (EGF) signaling. PBX1 regulates a subset of EGF-ERα genes highly expressed in aggressive breast tumours. Retrospective stratification of luminal patients using PBX1 protein levels in primary cancer further demonstrates that elevated PBX1 protein levels correlate with earlier metastatic progression. In agreement, PBX1 protein levels are significantly upregulated during metastatic progression in ERα-positive breast cancer patients. Finally we reveal that PBX1 upregulation in aggressive tumours is partly mediated by genomic amplification of the PBX1 locus. Correspondingly, ERα-positive breast cancer patients carrying PBX1 amplification are characterized by poor survival. Notably, we demonstrate that PBX1 amplification can be identified in tumor derived-circulating free DNA of ERα-positive metastatic patients. Metastatic patients with PBX1 amplification are also characterized by shorter relapse-free survival. Our data identifies PBX1 amplification as a functional hallmark of aggressive ERα-positive breast cancers. Mechanistically, PBX1 amplification impinges on several critical pathways associated with aggressive ERα-positive breast cancer.